Poligami dalam Perspektif Al-Qur’an - Al Haq, Mursyid (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
Polygamy is a phenomenon in human life that has occurred since ancient times. The presence of Islam in the midst of the ummah makes it also regulate and offer law as an effort to control socially that religion contributes, as well as as an answer to problems that occur in individual humans. So that polygamy is more accurately said to be a responsibility, a burden, or a solution that is a way out of a problem in certain situations and conditions. The statement that polygamy is a sunnah or religious recommendation is clearly baseless, because there is no evidence that states it. Attempts to decorate personal tendencies and desires with sharia or religious law have actually demeaned religious teachings which are so noble and noble, originating from Allah in order to direct human beings towards plenary benefit and happiness